Desarrollos y retos de la enfermería de práctica avanzada (2020)
Advanced Practice Nursing (APN) emerged as a response to the need for professionals capable of giving care to patients, thereby improving the quality of healthcare; the results obtained by implementing APNs in healthcare teams confirm that APNs can be implemented in the healthcare of patients of all ages and with varied health situations (1). Levels of development in APN are very diverse in distinct countries, in the legal aspect as well as in the roles that a nurse with this level of training can fulfill. The International Council of Nurses (ICN) counts around seventy countries as being preoccupied with introducing clear function for APNs (20); nonetheless, literature describes the main progress in this sense occurring in Canada, Australia, Ireland, Finland, the United Kingdom, and the United States, although in the last ten years significant advances have been identifies in Belgium, Germany, Switzerland, Thailand, Singapore, Korea, and Africa (3, 4). In Latin-American, progress in this initiative is embryonic: the role that a APN can fulfill has not been sufficiently disseminated and the implementation of this strategy has been limited by healthcare policies in many countries or by the opposition to APNs by professionals in other areas who are reacting to misinformation or to fear of usurpation of certain functions by APNs. However, in primary care, APNs have been incorporated into healthcare teams, and research shows positive results for the expansion of coverage and reduction of healthcare costs, in both rural areas and urban centers (1, 5). Thanks to these advances, in 2000 the ICN supported the creation of the International Nurse Practitioner/Advanced Practice Nursing Network (INP/APNN) with the objective of favoring dialogue, advancing the installation of APNs in the countries, facilitating the interchange of knowledge, determining the limits in the expansion of the role of nurses, and defining the guidelines for the formation of human resources at this level. Likewise, the World Health Organization and the Pan-American Health Organization (PAHO) have worked with universities and nursing associations in Latin America and the Caribbean to, through context analyses, propose implementation of APNs (5). During August 2018, the 10th Conference of the International Nursing Council convened in Rotterdam with the goal of exploring the role of APNs in the transformation of healthcare (6). With the participation of more than fifty countries, the council established a global panorama of the situation and of the challenges nursing faces as an active participant and agent for achieving universal health coverage. An important conclusion drawn from the event is the recognition given by all participating countries to APNs for allowing significant advancement of strategies for primary healthcare and the achievement of goals related with universal health coverage and sustainable development: the guarantee of a healthy life and the promotion of wellness for everyone at every age (4, 5). These propositions imply a process and the need for countries to work towards the expansion of nursing roles, which requires the promotion of a collective project that unites different sectors involved in the formation of human talent, on one hand, that the offering of health services on the other. Likewise, administrators of education and health policy along with associations involved in the nursing discipline need to contribute to the analyses of strategies for implementing a sustainable and efficient health system that allows universal access to health (1, 4, 7). In this context, APNs are understood to have undergone master or doctorate level training that develops scientific knowledge, clinical expertise, leadership, political formation, communicational capacity, and education for the patient, family, and community groups. Therefore, the professional is enabled to take ethical decisions, work autonomously, interact in intra- and interdisciplinary groups, and understand that ANP’s work will be determined by the unique environment, healthcare structure, and legislation of different countries. In accord with Morán-Peña (8), the International Nursing Council states that APNs are characterized by an autonomous practice that allows the implementation of tools like: valuation, diagnostic reasoning, decision making for the handling of cases, plan development, implementation and evaluation of programs as part of consultation services, and being the first point of contact in the healthcare system. This implies that an ANP will have competencies to participate in the elaboration of public policy as well as on teams dedicated to care for individuals, families, groups, and communities in disease prevention, health promotion, treatment, recuperation, and palliative care (7, 9, 10). Consequently, working on the implementation of the EPA can possibly lead to transformation of healthcare systems in the clinical area, improvement in the access to primary healthcare, and in the design and development of investigation projects whose results can be applied in practice; in short, it would affect the quality and effectiveness of healthcare at different levels and allow the urgent and much needed evolution of healthcare systems (11). With this perspective, the fundamental question is whether sufficient political interest exist for the development of APN’s roles, the definition of APN’s limits, the adaption of the existing structure, the establishment of guidelines for educational programs, and the application of expert knowledge, among other aspects, in benefit of health coverage, healthcare quality, and the establishment of a sustainable healthcare system.